Vaccination timeliness and associated factors among children aged 12–23 months in Debre Libanos district of North Shewa Zone, Oromia Regional State, Ethiopia - Dejene, Hiwot; Girma, Derara; Geleta, Leta Adugna; Legesse, Elsabeth (Frontiers in Pediatrics, 2022)
Background: Globally, vaccination is one of the most cost-effective interventions in promoting child survival, preventing 2-3 million child deaths annually from vaccine-preventable diseases (VPDs). In Ethiopia, timely vaccination is stated as key to preventing unnecessary childhood mortality from measles, pneumonia, diarrheal diseases, and other VPDs. However, Ethiopia ranked fifth among ten countries with the most unprotected children. Furthermore, previous vaccine timeliness studies produced widely disparate results. As a result, it was suggested that more research be conducted to investigate the potential factors behind the high proportion of untimely vaccination. Therefore, this study was intended to explore the association between different factors and the proportion of vaccination timeliness administered under the Expanded Program on Immunization in Debrelebanos district, Ethiopia. Methods: A community-based cross-sectional study design was employed from May 01 to 30 2021 among children aged 12 to 23 months with their mother/caregiver, who had started vaccination and had vaccination cards in the Debrelebanos. A simple random sampling technique and pretested semi-structured questionnaires were used for data collection. Finally, multivariable logistic regression was used to identify factors associated with the vaccination timeliness. Result: In this study, 413 children aged 12 to 23 months were interviewed with their mother/caregiver. Overall, 33.7% [95% CI (29.1-38.3)] of children received their vaccines timely. Having a female child [AOR: 2.9, 95% CI: 1.58-5.35], mother/caregiver attending primary [AOR: 6.33, 95% CI: 2.66-15.06] and secondary/above education [AOR: 5.61, 95% CI: 2.41-13.04], sufficient vaccination knowledge [AOR: 3.46, 95% CI: 1.87-6.38], mother/caregiver with least hesitant [AOR: 3.35, 95% CI: 1.51-7.41] and middle hesitant [AOR: 1.89, 95% CI: 1.05-3.58], utilization of ANC [AOR: 2.89, 95% CI: 1.32-6.33], and giving birth at health facility [AOR: 4.32, 95% CI: 1.95-9.59] were the factors significantly associated with vaccination timeliness. Conclusion: The proportion of children immunized at the recommended time interval is low in the study district. Therefore, emphasis should be placed on mother/caregiver education level, child sex, vaccination knowledge and hesitancy, ANC utilization, and place of birth. Additionally, policymakers should prioritize vaccine timeliness and reinforce its integration into childhood vaccination strategies.